The Effect of Soluble CD14 Subtype (sCD14ST)/ Presepsin and Lactate Clearance on Mortality Status In Pneumonia Patients With Sepsis - Zikanovelia Zikanovelia; Ngakan Putu Parsama Putra; Yani Jane Sugiri; Harun Al Rasyid (Indonesian Society of Respirology (ISR), 2021)
Background: Severe pneumonia accompanied with sepsis could increase death ratio by 7.6%. Lactate clearance is used in assessing the success of early resuscitation in treating sepsis. Presepsin is a biomarker that is sensitive and specific to the bacterial infection that causes sepsis. The purpose of this study was to analyze the effect of presepsin levels and lactate clearance on mortality in pneumonic patients accompanied with sepsis after fourteen day of observation. Methods: Prospective cohort study was done on 42 patients who were admitted to intensive care unit of dr. Saiful Anwar Public Hospital, from March 2019 until May 2019. Blood samples were collected on the first, second, and third day of treatment to measure lactate clearance and presepsin levels. Mortality was observed on the 14th day after admittance. Results: Out of 42 patients, 25 patients lived (59.5%), and 17 patients died (40.5%). Logistic regression analysis performed on the presepsin levels on the third day with a cut-off 957 ng/L had a significant effect on mortality after 14th day (p=0.034). However, presepsin levels on the first day with a cut-off 957 ng/L had no significant effect on mortality (p=0.24). Likewise, the lactate clearance with cut-off 10% did not significantly influence the mortality status (p=0.136). Conclusion: There is a significant effect between presepsin level on the third day in patient mortality, however lactate clearance and presepsin level assessed on the first day had no significant effect on the mortality after fourteen day of observation.